2019
DOI: 10.3846/btp.2019.36
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cultural Orientation on the Entrepreneur Competencies in the Globalization Era

Abstract: The existence of globalization concept absolutely brings consequences for business environment. Based on international literature, cultural orientation was required on business management in the globalization era. Nevertheless, there have been few numbers of cross-cultural entrepreneurship research. Previous research tended to focus on discussing cultural dimensions or using them in entrepreneurship. Therefore, this study proposes a different perspective which is to explore the cultural dimensions for the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Conceptual understanding and terminology related to generic competencies have varied, in particular at the higher education level (Solesvik, 2019;Mutiara et al, 2019;Šafránková & Šikýř, 2018). Billing (2003) researched standard graduate competencies required for jobs in various countries and found that skills can be exported to different countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conceptual understanding and terminology related to generic competencies have varied, in particular at the higher education level (Solesvik, 2019;Mutiara et al, 2019;Šafránková & Šikýř, 2018). Billing (2003) researched standard graduate competencies required for jobs in various countries and found that skills can be exported to different countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The era of globalization is filled with a set of processes of change in the economic, social, cultural, technological, and institutional fields, which contributes to relationships between individuals worldwide (Sicca, 2021;Tolchah & Mu'ammar, 2019;Mutiara et al, 2019). It comes with a few benefits on personal and social levels (Mutiara et al, 2019).…”
Section: Globalization Eramentioning
confidence: 99%
“…The era of globalization is filled with a set of processes of change in the economic, social, cultural, technological, and institutional fields, which contributes to relationships between individuals worldwide (Sicca, 2021;Tolchah & Mu'ammar, 2019;Mutiara et al, 2019). It comes with a few benefits on personal and social levels (Mutiara et al, 2019). In personal terms, it opens up the opportunity for every individual to gain knowledge through various media, master foreign languages from television programs and contents over the Internet, develop creativity, and improve learning abilities (V. K. M. P.…”
Section: Globalization Eramentioning
confidence: 99%
“…This dimension is important in entrepreneurship studies because of the theoretical link between the tolerance of uncertainty and risk taking (Beugelsdijk et al, 2017;Laskovaia et al, 2017;Valliere, 2017) which implies that individuals with a low Uncertainty avoidance will show a greater propensity to start up new businesses (Calza et al, 2020). Although the link between the ability to cope with uncertainty and entrepreneurial activity has empirical support (Naqvi & Siddiqui, 2020;Canestrino Magliocca & Pawelek, 2020), there are findings to the contrary (Lee & Kelly, 2019;Mutiara et al, 2019).…”
Section: Uncertainty Avoidancementioning
confidence: 99%
“…It is apparent from the paragraph above that many of the studies consider the cultural dimensions independently and this is one of the major quandaries in the study of culture, (Irene, 2016;Mutiara et al, 2019;Shiri et al, 2017;Valliere, 2017;Williams & McGuire, 2010).…”
Section: Culture and The Theory Of Planned Behaviourmentioning
confidence: 99%